Updates to the validity evidence based on the internal structure of the ASRS-18 - Porto, Thiago Iamada (2023)
The aim of this research was to present updated validity evidence based on the internal structure of the ASRS-18. Two studies were carried out, an exploratory factor analysis (EFA) and a confirmatory factor analysis (CFA). In the opposite direction to what the literature suggests for the instrument, the EFA indicated the adequacy of the one-factor model, which supported the decision regarding the number of factors to be retained. Once the structure of the scale had been determined, CFA and multi-group CFA analyses were carried out to assess the characteristics of the instrument. The results obtained in the CFA were initially unsatisfactory, with items having high residual correlations, explained by the redundancy of content between items. It was therefore decided to reduce the number of items in the instrument, and the analyses indicated that the scale was suitable for use in both clinical practice and research. Finally, the multi-group CFA showed that the gender variable influenced the scale's response pattern, with women needing a greater latent trait to score higher on the inattention items and a lower trait for the hyperactivity items. The proposed ASRS-18 presents an accurate and stable model for measuring attention deficit hyperactivity disorder (ADHD). It is suggested that a reduced version of the instrument be used, as well as further research to expand the evaluation of psychometric properties. In the clinical sphere, it is recommended to consider the suggestions presented in the discussions of this study for assessing ADHD symptoms for criterion A according to the DSM.